Fostering Grade 3 Students' Reading Interest: The One Day One Reading Literacy Movement - Faizatul Widat; Uswatun Hasanah; Arini Izzatin Nabila (Educazione: Journal of Education and Learning, 2023)
This study examines the application of the One Day One Reading (ODOR) method in increasing the reading interest of grade 3 students at MI Azzainiyah II Karanganyar. The primary focus of this study is to explore the impact of daily reading activities carried out before lessons start, as well as the challenges faced while applying this method. This study uses a qualitative approach with a case study type, data collected through interviews, class observations, and documentation analysis. The findings of the study show that although ODOR has succeeded in increasing students' interest in reading, time constraints and book diversity are important factors that affect the program's success. In addition, home environment support, such as the role of parents in accompanying reading activities, has also been proven to increase the success of ODOR. The implications of these findings provide important insights for developing more flexible and effective literacy programs at the elementary school level and improving understanding of the factors that influence students' reading habits.